Safety, tolerability, pharmacokinetic/pharmacodynamic characteristics of bersiporocin, a novel prolyl‐tRNA synthetase inhibitor, in healthy subjects - Min Young Park; Sungyeun Bae; Jung A Heo; Mihee Park; YuKyung Kim; Jumi Han; In‐Jin Jang; Kyung‐Sang Yu; Jaeseong Oh (Wiley, 2023)
Abstract Bersiporocin, a novel first‐in‐class prolyl‐tRNA synthetase (PRS) inhibitor currently under clinical development, was shown to exert an antifibrotic effect through the downregulation of collagen synthesis in various pulmonary fibrosis models. The aim of this first‐in‐human, randomized, double‐blind, placebo‐controlled, single‐ and multiple‐dose, dose‐escalation study was to evaluate the safety, tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of bersiporocin in healthy adults. A total of 40 and 32 subjects were included in a single‐ (SAD) and multiple‐ascending dose (MAD) study, respectively. No severe or serious adverse events were observed after a single oral dose up to 600 mg and multiple oral doses up to 200 mg twice daily for 14 days. The most common treatment‐emergent adverse events were gastrointestinal adverse events. To improve the tolerability, initial bersiporocin solution was changed to the enteric‐coated formulation. Afterward, the enteric‐coated tablet was used in the last cohort of SAD and in the MAD study. Bersiporocin showed dose‐proportional PK characteristics after a single dose up to 600 mg and multiple doses up to 200 mg. Upon reviewing the safety and PK data, the final SAD cohort (800 mg enteric‐coated tablet) was canceled by the Safety Review Committee. The levels of pro‐peptide of type 3 procollagen were lower after treatment with bersiporocin than after the placebo in the MAD study, whereas no significant change was observed in other idiopathic pulmonary fibrosis (IPF) biomarkers. In conclusion, the safety, PK, and PD profile of bersiporocin supported its further investigation in patients with IPF.